2006
DOI: 10.1128/aac.50.4.1170-1177.2006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Rifampin, Isoniazid, Pyrazinamide, and Ethambutol Pharmacokinetics in a Cohort of Tuberculosis Patients

Abstract: Evaluation of sources of pharmacokinetic variation can facilitate optimization of tuberculosis treatment regimens by identification of avoidable sources of variation and of risk factors for low or high drug concentrations in patients. Our objective was to describe the pharmacokinetics of rifampin, isoniazid, pyrazinamide, and ethambutol in a cohort of tuberculosis patients established on first-line treatment regimens and to evaluate the determinants of pharmacokinetic variation. Plasma concentration-time profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
234
5
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(269 citation statements)
references
References 23 publications
28
234
5
2
Order By: Relevance
“…[19] Furthermore, McIlleron and co-workers demonstrated a wide variation in plasma concentrations of rifampicin, with almost 70% of the study group at the lower end (<8 µg/l) and 22% at the very low end (<4 µg/l) of the therapeutic range. [20] Kimerling et al reported very similar findings, 64% of subjects having levels below 8 µg/l for rifampicin. [21] In a cohort of patients, the majority of whom were HIV-infected, Chideya et al …”
Section: Discussionsupporting
confidence: 65%
“…[19] Furthermore, McIlleron and co-workers demonstrated a wide variation in plasma concentrations of rifampicin, with almost 70% of the study group at the lower end (<8 µg/l) and 22% at the very low end (<4 µg/l) of the therapeutic range. [20] Kimerling et al reported very similar findings, 64% of subjects having levels below 8 µg/l for rifampicin. [21] In a cohort of patients, the majority of whom were HIV-infected, Chideya et al …”
Section: Discussionsupporting
confidence: 65%
“…Moussa et al [11] determined that the INH concentration in 3 h post-dose samples was below the reference range in 54 % of 13 TB patients. Our results, together with the results of other studies [18,19], indicate the importance of analyzing a series of blood samples to obtain the maximum blood concentrations of INH and PZA. Relying on one sample taken at a specific time, such as the 2 or 3 h post dose, is likely to yield a false high percentage of patients with low levels of these drugs, particularly INH.…”
Section: Discussionsupporting
confidence: 50%
“…McIlleron et al [18] reported that the median C max of INH was 6.5 mg/L, and only 2 % of 142 patients had C max of INH level less than 3 mg/L. The median C max of PZA was 52.7 mg/L, and only one patient (0.7 %) had C max of PZA less than 20 mg/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, CSF penetration of rifampicin, the key drug in TBM treatment, is poor, as is that of ethambutol and streptomycin [75][76][77]. Isoniazid and pyrazinamide penetrate more readily [78,79].…”
Section: Specific Antituberculous Treatmentmentioning
confidence: 99%